TRANSFORMATION OF ECONOMIC SYSTEM IN POLAND - Savyts’ka, Svitlana (Journal of European Economy, 2017)
The paper studies peculiarities of market transformation in Poland. The stages of transition period are highlighted. The regularities are accentuated; likewise methods and technique for implementation of Polish practice, as well as positive and negative consequences of the chosen strategy are analyzed.